Waist‐to‐height ratio remains an accurate and practical way of identifying cardiometabolic risks in children and adolescents - Jiang, Yuan; Dou, Ya‐lan; Xiong, Feng; Zhang, Lan; Zhu, Gao‐hui; Wu, Ting; Zhang, Yi; Yan, Wei‐li (Acta Paediatrica, 2018)
Aim We evaluated how effectively the waist‐to‐height ratio (WHtR) identified cardiometabolic risk (CMR) in children and adolescents, compared with the tri‐ponderal mass index, percentage of body fat and other obesity indexes. Methods Eligible subjects were recruited from three metropolitan regions of China from May 2013 to June 2014. Subjects with at least three of the following abnormalities – hypertension, dyslipidemia, elevated fasting blood glucose and central obesity – were defined as CMR1 and children with at least two were defined as CMR2. The area under the curve (AUC) of the receiver operating characteristic curve was used to compare how effectively obesity indexes predicted CMR. Results We recruited 3556 subjects aged 7–18 years. All five obesity indexes showed good, comparable performances in identifying CMR and the AUCs ranged from 0.89 to 0.90 for CMR1 and 0.83 to 0.85 for CMR2. The cut‐off of 0.467 for WHtR achieved a sensitivity of 0.91 and specificity of 0.80 for predicting CMR1, with the best cut‐offs being 0.463 for boys and 0.469 for girls. Conclusion The WHtR was a superior and practical screening tool for detecting CMR in this paediatric population, as it provided comparable accuracy to other methods and just required a simple calculation.